A comparison of Value at Risk and Expected Shortfall estimation models in the time before the COVID-19 pandemic - Taweesoontorn, Natcha (2020)
This dissertation aims to examine the performance of different risk measures with three international indices: S&P 500, FTSE250 and HSI. The study compared four distribution candidates used in modelling the Value at Risk (VaR) and expected shortfall (ES) estimates with 95% significant level aiming to analyse the quality of them in producing 1-day ahead forecasts as well as consider the more accurate prediction when the index returns have their volatility conditioning with GARCH model. The VaR and ES forecasts were computed from unconditional and conditional models applied to four distribution candidates which were the Historical Simulation, the Gaussian model, the Student-t distribution as well as Generalised Pareto distribution using extreme value theory.